Prevalence of monoclonal gammopathy in patients presenting with acquired angioedema type 2 - Frémeaux-Bacchi, Véronique; Guinnepain, Marie-Thérèse; Cacoub, Patrice; Dragon-Durey, Marie-Agnès; Mouthon, Luc; Blouin, Jacques; Cherin, Patrick; Laurent, Jérome; Piette, Jean-Charles; Fridman, Wolf-H; Weiss, Laurence; Kazatchkine, Michel O (The American journal of medicine, 2002)
Acquired angioedema type 1 is characterized by a C1 inhibitor deficiency in patients with lymphoproliferative disorders, whereas acquired angioedema type 2 is characterized by anti-C1 inhibitor antibodies, and has not been thought to be associated with lymphoproliferative disease. We studied the clinical features, complement profiles, and associated diseases in 19 new patients with diagnosed acquired angioedema type 2. Plasma concentrations and functional activity of complement components were measured by conventional techniques. Functional C1 inhibitor activity was assessed by a chromogenic assay. Autoantibodies to C1 inhibitor were detected using an enzyme-linked immunosorbent assay. The 11 men and 8 women (median age, 60 years) presented with recurrent attacks of angioedema. All patients had detectable anti-C1 inhibitor antibodies in serum. A monoclonal gammopathy was detected in 12 patients (63%) at the time of diagnosis, 11 of whom had an immunoglobulin peak of the same heavy- and light-chain isotypes as the acquired anti-C1 inhibitor antibody. Three of these 12 patients developed a malignant lymphoproliferative disease. As with type 1 disease, a large proportion of patients with acquired angioedema type 2 have a lymphoproliferative disorder.